A method to quantify coating thickness and porosity of electrodes for lithium-ion-batteries. (July 2016) - Just, Ph.; Rost, J.; Echelmeyer, T.; Ebert, L.; Roscher, M.A.
Highlights: Evaluation of thermography based electrode inspection. Changes in thickness and porosity of electrodes are detectable. Active thermography is applicable for in-line electrode inspection. Abstract: For manufacturing the electrodes of lithium-ion batteries a active material slurry is casted onto a metallic foil and dried, thereafter. Due to stringent quality requirements regarding the porous layer of active material control systems are implemented in the production line which are capable to detect contaminations and check the homogeneity of the active material film application. This work presents the active thermography as method for real time testing of electrodes' active layer thickness and basis weight. In experimental investigations a correlation between the electrodes' thermal characteristics and the geometry could be found, confirming that: First, thin films with a high porosity heat up faster, during thermal excitation, than thicker and more compressed films. Second, denser electrodes comprise a higher thermal conductivity and hence heat up and cool down slower than films comprising higher porosities. Both aspects are crucial findings and enable the development of innovative in-line electrode inspections systems.